Olive genetic resources in Tunisia : Diversity and valorization - Fathi Ben Amar; Mohamed Ayadi; Abdelmajid Yengui; Hassan Belguith (Journal of Pure & Applied Sciences, 2022)
The olive plantation in Tunisia is very ancient, which resulted in a great genetic diversity that was preserved in the olive collection in the Tunisian city of Sfax (rainy regime and arid climate). The collection contains 145 local varieties and 53 foreign varieties from 11 countries at present. The olive productivity in the period 2007-2019 proves a diversity in the rates from 0.46 to 20.06 kg/tree and indicates the presence of high-yielding local varieties with variable alternate bearing. In terms of the oil acidic composition, the analyzes showed the presence of 14 varieties with high oleic acid content (>70%) and medium contents for palmitic and linoleic acids, making them of high quality and conformed to commercial and health specifications and distinct from the reference variety in Tunisia ’Chemlali Sfax’. Choosing distinct olive varieties from the Bougrara collection will increase olive production in Tunisia and improve the oil quality for greater export opportunities.